Dihydropyrimidinones Against Multiresistant Bacteria - Castro Jara, Marisa; Silva, Allison Carlos Assunção; Ritter, Marina; da Silva, Adriana Fernandes; Gonçalves, Carolina Lambrecht; dos Santos, Pedro Rassier; Borja, Luciano Sisconetto; de Pereira, Cláudio Martin Pereira; da Silva Nascente, Patrícia (Frontiers in Microbiology, 2022)
The increase in bacterial resistance to antimicrobials has led to high morbidity and mortality rates, posing a major public health problem, requiring the discovery of novel antimicrobial substances. This study evaluated in vitro the antimicrobial activity of three synthetic DHPM analogues against multi-drug resistant bacterial isolates from hospital patients. The biological samples were identified as the Gram-negative bacilli Acinetobacter baumannii, Escherichia coli, Enterobacter cloacae, Klebsiella pneumoniae, Morganella morgannii, Pseudomonas aeruginosa and Serratia marcescens and the Gram-positive cocci Enterococcus faecium and Staphylococcus aureus, all of them resistant to at least three classes of antimicrobials. The antibacterial activity of the compounds was checked in vitro by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) by the broth microdilution method and plating in brain heart infusion (BHI) agar, respectively (CLSI, 2012). The chemical characterization of the compounds was performed by measuring the melting point and gas chromatography coupled with mass spectrometry (GC-MS) on a Shimadzu GC-MS-QP system 2010SE. Synthetic compounds showed antimicrobial activity against Gram-positive cocci at MIC concentrations 0.16-80 μg / mL and Gram-negative bacilli at MIC concentrations 23.2-80 μg / mL. E. faecium and S. aureus had the best MIC values. The results of the cytotoxicity test indicated that the synthetic compounds showed no significant difference in three concentrations tested (5, 20 and 80 μg/mL), allowing cell viability not different from that assigned to the control, without the tested compounds. In this context, the development of DHPM derivatives brings an alternative and perspective on effectiveness of drugs as future antimicrobial agents.